1983
DOI: 10.1002/bip.360220142
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the structure of bovine seminal ribonuclease

Abstract: SynopsisWe report here the refinement at 2.5-A resolution of the x-ray crystal structure of bovine seminal rihonuclease, a dimeric covalent enzyme. The protein, which crystallizes with one molecule in the asymmetric unit, consists of two subunits of identical chemical sequences, related by an almost exact binary axis. The tertiary structure of the subunits is similar to that of the pancreatic enzyme, which shows similar catalytic properties. The refinement was carried out using the restrained least-squares pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…The initial scFv-BSRNase fusion protein construct consisted of a straightforward linkage of the C-terminus of the scFv V K region to the native BSRNase N-terminus. This site was chosen as examination of the three-dimensional structure indicated that the C-terminus was less accessible (Capasso et al, 1983). The amplification oligonucleotides were designed to produce a BSRNase cassette with an N-terminal XhoI site followed by a IleLys-Arg sequence to replace the same sequence found at the end of the scFv ( Figure IA).…”
Section: Enzyme-linked Immunosorbent Assays and Western Blotsmentioning
confidence: 99%
“…The initial scFv-BSRNase fusion protein construct consisted of a straightforward linkage of the C-terminus of the scFv V K region to the native BSRNase N-terminus. This site was chosen as examination of the three-dimensional structure indicated that the C-terminus was less accessible (Capasso et al, 1983). The amplification oligonucleotides were designed to produce a BSRNase cassette with an N-terminal XhoI site followed by a IleLys-Arg sequence to replace the same sequence found at the end of the scFv ( Figure IA).…”
Section: Enzyme-linked Immunosorbent Assays and Western Blotsmentioning
confidence: 99%
“…The presence of Leu 28 in BS-RNase, rather than a glutamine residue in RNase A, makes this region highly hydrophobic and thus facilitates the contact between the two subunits (Capasso et al, 1983). Lys 34 of BS-RNase is responsible for the high reactivity of Cys 31 and Cys 32 toward reducing agents (Parente et al, 1985).…”
mentioning
confidence: 99%
“…Recent results (unpublished) indicate that the amide group in question is that of Asne,. This residue is far away from the subunit active site and also from the intersubunit region, as shown by the tri-dimensional structure of the protein [21]. Thus it would seem very unlikely that the side chain of this residue could affect the catalytic act of the reaction, without significantly affecting the K,, i.e., the binding of substrate.…”
Section: Discussionmentioning
confidence: 97%